2017
DOI: 10.1103/physrevlett.119.223901
|View full text |Cite
|
Sign up to set email alerts
|

Phase Memory Preserving Harmonics from Abruptly Autofocusing Beams

Abstract: We demonstrate both theoretically and experimentally that the harmonics from abruptly autofocusing ring-Airy beams present a surprising property: They preserve the phase distribution of the fundamental beam. Consequently, this "phase memory" imparts to the harmonics the abrupt autofocusing behavior, while, under certain conditions, their foci coincide in space with the one of the fundamental. Experiments agree well with our theoretical estimates and detailed numerical calculations. Our findings open the way fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Nonlinear three-wave mixing process have also been employed in the generation of an Airy beam from a pump under phase matching conditions [100,101]. During harmonic generation of abruptly autofocusing beams it was shown that the high harmonics preserve the phase distribution of the fundamental beam [102].…”
Section: Nonlinear Dynamicsmentioning
confidence: 99%
“…Nonlinear three-wave mixing process have also been employed in the generation of an Airy beam from a pump under phase matching conditions [100,101]. During harmonic generation of abruptly autofocusing beams it was shown that the high harmonics preserve the phase distribution of the fundamental beam [102].…”
Section: Nonlinear Dynamicsmentioning
confidence: 99%
“…And the authors generated the multi-focus auto-focusing beams at the focusing plane by modifying the frequency spectrum of a symmetric Airy beam with a Gaussian band elimination filter [23]. Unlike the multi-focus CABs with off-axis focus at the focusing plane, there are methods to generate the multifocusing beams along the optical axis, such as by introducing two different initial launch angles [24], under the action of a converging lens [25][26][27][28], and by introducing hyperbolic umbilic function modulation [29]. Despite existing methods for modulating CABs to generate multi-focal abruptly autofocusing beams, it is still difficult to obtain multi-focus autofocusing beams with equal intensity focus along the optical axis.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, cylindrically symmetric Airy beams were introduced with unexpected abrupt autofocusing [36,37], known as autofocusing beams or ring-Airy beams [38]. These novel wavepackets and their variations [39][40][41][42], were ideal for various applications like trapping and guiding microparticles [43], phase memory preservation [44], and fabrication of large three-dimensional structures [45]. Recently, Airy beams that carry OAM were investigated.…”
Section: Introductionmentioning
confidence: 99%